Stenochrus portoricensis (Arachnida: Schizomida) living in a nest of the fire ant Solenopsis saevissima (Hymenoptera: Formicidae) in the Atlantic Forest, Brazil - Migliorini, Gustavo H. [UNESP] (2019)
Schizomida is an arachnid order widely distributed in tropical and subtropical regions, commonly found in humid and warm environments such as leaf litter, on the underside of rocks, and in caves. Stenochrus portoricensis has been observed in association with termite and ant nests. In this study, we report for the first time S. portoricensis living within a nest of the fire ant Solenopsis saevissima. This new interaction triggers interest in the mechanisms used by the schizomid to deceive and be undetected by fire ants, as well as the potential advantages for the schizomid in living within Solenopsis nests.